Artropodofauna em cultivo associado de roseira e girassol - Barros, Igor de Carvalho (2015)
The objective of the present work was to evaluate the influence of the sunflower as attractive plant in the distribution of arthropods in a system associated with roses disposed at different distances. The experiment was conducted at the Department of Entomology of the Universidade Federal de Lavras (UFLA), in a 15 x 5 m area, covered with 50% shading material. The treatments constituted of rose vases disposed in three lines on each side of a central line comprised of sunflower vases, distanced at: A) 1 m, B) 3.5 m and C) 6 m. Samplings of arthropods were performed in all the aerial part of both botanic species, during 35 days, with the aid of an entomological sucker. The data were submitted to faunal analysis, calculating the collection curves. The ecologic indexes obtained for grouping the identified taxons showed differences in abundance and richness in function of the treatments. W verifies lower population density of phytophagous species in rose vases located near the sunflower vases. Treatment A presented higher arthropod richness (26 taxons) in relation to the treatments more distanced from the central line (B and C). The incorporation of sunflower associated to rose culture emerges as an important tool for maintaining benefic insects, contributing for herbivore control in the system.